The reality of the practice of science teacher at the primary level Principles of constructivism theory from the point of view of the supervisors of the book of science - Ramla Jabbar Kadhim AL _ Saedi / Ahmed Abdul-Reda Murad Al-Sharifi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The current research aims to know the reality of science teachers’ practice in the primary stage of the principles of constructivist theory from the point of view of the subject supervisors. To achieve the objectives of the study, the researchers used the descriptive approach (work analysis) and the study sample consisted of (72) As a supervisor and supervisor, they prepared a questionnaire consisting of (41) items distributed on (6) previous knowledge of learners, implementation of the lesson with the participation of learners, learning science is an active constructive process, learning takes place through social dialogue, employing the environment and the local community as a source of learning, evaluating learners, To treat the data statistically, the researchers used the percentage, standard deviations, and weighted means. After analyzing the data, the researchers concluded that the level of practice of science teachers in the elementary school for the principles of constructivist theory was moderately high. This result is not at the level hoped for to achieve educational outcomes characterized by efficiency and high quality, and that some of the principles of the constructivist theory were practiced to a moderate degree and others came at a low level of practice, and perhaps the principle related to Perhaps the principle related to (learning takes place through social dialogue) was at the bottom of the relative order among the rest of the principles in terms of the degree of practice.